2014
DOI: 10.1111/clr.12479
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissues stability of cad‐cam and stock abutments in anterior regions: 2‐year prospective multicentric cohort study

Abstract: In the anterior area, the use of cad-cam abutments is related to a better soft tissue stability. Such a relationship is significant if cad-cam titanium abutments are compared to both titanium and zirconia stock abutments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 24 publications
1
62
0
Order By: Relevance
“…Although the crowns were retained by cross‐pin, leakage and plaque accumulation may still occur and lead to soft tissue redness and inflammation. Such observation corroborates the outcome of earlier studies that reported advantages of the CAD/CAM abutment in maintaining soft tissue contour . Nevertheless, it is important to note that the biological differences between the two protocols were very minor and may not be of clinical significance or lead to biological and esthetic failure.…”
Section: Discussionsupporting
confidence: 90%
“…Although the crowns were retained by cross‐pin, leakage and plaque accumulation may still occur and lead to soft tissue redness and inflammation. Such observation corroborates the outcome of earlier studies that reported advantages of the CAD/CAM abutment in maintaining soft tissue contour . Nevertheless, it is important to note that the biological differences between the two protocols were very minor and may not be of clinical significance or lead to biological and esthetic failure.…”
Section: Discussionsupporting
confidence: 90%
“…All studies reported on customized Ti and Zr abutments, and one study also provided data on stock Zr and Ti abutments (Lops et al. ). Due to marked heterogeneity in the study design and quality of reported data, statistical meta‐analysis was only feasible for peri‐implant soft tissue color outcome measure.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proven that the practitioner's perspective is different than that of the patients . The importance of using computer‐aided design and computer‐aided manufacturing (CAD/CAM) to reproduce a favorable shape of the abutment that would support the peri‐implant soft tissue and ensure better esthetics was discussed …”
mentioning
confidence: 99%